Kunst en Expressionisme - Louwers, Frans (Wondelgem : Gemeentelijke Kulturele Raad, 1973)
Cantre, Jozef ; De Buck, Evarist ; De Smet, Gustave ; De Smet, Leon ; Poetou, Emiel ; Saverijs, Albert ; Servaes, Albert ; De sutter, Jules ; Malfait, Hubert ; Permeke, Constant ; Van den Berghe, Frits ; Wolvens, Victor-Henri
Nederlands
boek